Reducing Energy Consumption Using DOE and SPC on Cork Agglomeration Line - Hugo Silva; André S. Santos; Leonilde R. Varela (Clean Technologies)
The industrial landscape has revealed two trends: increased competitiveness and a greater demand for sustainable solutions. Materials with cork in their composition are an appealing solution, since they guarantee the desired mechanical characteristics while contributing to the prevention of environmental degradation. Given the change in external factors, there has been a substantial rise in energy costs. Thus, it is essential to optimize processes, with the aim of reducing the consumption of resources, such as electricity. This project was developed at a company that manufactures cork blocks, sheets, and rolls. Regarding blocks, a critical operation of this line is the high-frequency heating, being the bottleneck of this work center. With the critical variables previously identified, planned experiments were conducted based on DOE’s full factorial methodology. Two out of four products revealed inputs with statistical significance. With these results, a reduction in parameters was implemented in the factors and interactions that showed no statistical significance. Finally, average and amplitude control charts, based on the SPC methodology, were applied to solidify and guarantee the quality of the agglomerated blocks, with the parameter changes already introduced. The company benefited from this study by having a significant reduction in its energy consumption.